Clinical evaluation of surface treatment on clinical performance of non-carious sclerotic cervical lesions: 18-month follow-up. - Alencar, Christiane de M; Fernandes, Gabriela C S; Barros, Antonio Patrícia O; Zaniboni, Joissi F [UNESP]; Silva, Aryvelto M [UNESP]; Jassé, Fernanda F de A; Silva, Cecy M; Campos, Edson A de [UNESP] (My University, 2023)
PURPOSE: To evaluate the influence of different surface treatments on the clinical behavior of non-carious cervical sclerotic lesions (NCCLs) over an 18-month follow-up period. METHODS: 128 NCCLs from 32 volunteers were randomized into four groups (n=32): G1-control, without preoperative treatment of the dentin surface; G2, dentin conditioning with 17% ethylenediaminetetracetic acid (EDTA) for 2 minutes; G3, increase in dentin surface roughness with diamond bur and G4, increase in dentin surface roughness with diamond bur + dentin conditioning with 17% EDTA for 2 minutes. RESULTS: Differences between groups were tested using the Friedman test (α= 0.05). A questionnaire was administered to volunteers about risk factors related to NCCLs. The relationship between the questionnaire data and the clinical performance of the restorations was analyzed using the multiple logistic regression test (α= 0.05). The variables related to parafunctional habits, anxiety and/or depression were significantly related to the manifestation of postoperative sensitivity. Roughening the sclerotic dentin with a diamond bur increased postoperative sensitivity within 12 months. The presence of parafunctional habits and anxiety/depression may lead to postoperative sensitivity. CLINICAL SIGNIFICANCE: Roughening the sclerotic dentin with a diamond bur increased postoperative sensitivity within 12 months.